ANALYSIS OF THE INDUSTRIAL OBJECTS RENOVATION EXPERIENCE - Semko, О. V.; Voskobiynyk, Ye. P. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Examples of foreign and domestic experience of renovation the industrial objects are considered. It is shown that in the European Union countries for the last 30 years, according to statistic research, the new construction and renovation index has increased. For the European practice, the expantion of renovation process from typical neutral objects to monuments of industrial architecture is a common thing. It has been noted that domestic practice is usually characterized by the composition of trading and office rooms in the environment of adaptation the typical neutral objects of industrial estate. Analysis of the examples showed that the renovation utilizes structural and planning, as well as aesthetic potential of the industrial buildings. Analysis results allow identifycation the options and directions for converting the inoperable industrial objects into civil buildings. This experience might be utilized for development the rational architecture-planning and structural solutions for reconstruction.
Keywords: renovation; inoperable building; reconstruction; converting